ANALISIS KUALITAS AIR DALAM PENENTUAN LOKASI BUDIDAYA RUMPUT LAUT (Eucheuma cottonii) DI KAWASAN TELUK PAREPARE - Damis Damis; Muhammad Saenong (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2020)
This study aims to determine land suitability for seaweed cultivation in the Parepare Bay Region, assessing the feasibility of developing seaweed cultivation; identify factors that influence the development of seaweed cultivation; Conformity evaluation conducted in this study is the actual suitability or suitability of seaweed cultivation land, where the resulting land suitability class is only based on available data, not considering social, economic, financial, and other aspects. The research method used is a direct survey at the research location. The results of the land suitability analysis are based on the suitability matrix: spatial data analysis using the Geogerafis Information System method, to determine the suitability of seaweed cultivation land. The results showed that the area of land suitability for seaweed cultivation based on the land suitability map was appropriate (S) ± 578.57 ha and not suitable (N) ± 759.68 ha